2012
DOI: 10.1901/jeab.2012.98-311
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive and Facilitative Effects of Shock Intensity and Interresponse Times Followed by Shock

Abstract: Although response‐dependent shock often suppresses responding, response facilitation can occur. In two experiments, we examined the suppressive and facilitative effects of shock by manipulating shock intensity and the interresponse times that produced shock. Rats' lever presses were reinforced on a variable‐interval 40‐s schedule of food presentation. Shock followed either long or short interresponse times. Shock intensity was raised from 0.05 mA to 0.4 mA or 0.8 mA. Overall, shock contingent on long interresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…In the Arbuckle and Lattal study, the avoidance response was a particular spacing of responses on the same operandum as the punished response. As the duration of interresponse times among punished responses can be selectively modified by punishment contingencies alone (Everly & Perone, 2012;Galbicka & Branch, 1981), the present study extended the analysis to assess the effects of punishment and avoidance with contingencies arranged on different levers (topographical tagging, Catania, 1973).…”
mentioning
confidence: 99%
“…In the Arbuckle and Lattal study, the avoidance response was a particular spacing of responses on the same operandum as the punished response. As the duration of interresponse times among punished responses can be selectively modified by punishment contingencies alone (Everly & Perone, 2012;Galbicka & Branch, 1981), the present study extended the analysis to assess the effects of punishment and avoidance with contingencies arranged on different levers (topographical tagging, Catania, 1973).…”
mentioning
confidence: 99%
“…Galbicka and Branch (1981), for example, suggested that "interval schedules of punishment may differentially punish long IRTs" therefore resulting in a greater proportion of short IRTs, leading to increases in response rate (p. 320). More recently, Everly and Perone (2012) showed that increases or decreases in response rates during shock punishment may be multiply determined by the schedule values of punishment and reinforcement, the duration and intensity of the shock, and the IRTs followed by shock.…”
Section: Schedule Effects Of Timeout Punishment In Relation To Positimentioning
confidence: 99%
“…Dunn found response reduction relative to notimeout conditions for all three schedules of timeout. The finding that interval schedules of timeout can decrease response rates within a multiple schedule arrangement adds to the generality of response reduction by timeout punishment.In prior experiments, differences in the punished IRTs have not only increased or decreased response rates, but also changed particular classes of IRTs dependent on whether short or long IRTs are targeted for punishment(Arbuckle & Lattal, 1992;Everly & Perone, 2012;Galbicka & Branch, 1981). For example, Everly and Perone found that shock dependent on long IRTs generally increased response rates and, conversely, when shock was dependent on short IRTs response rates decreased; the IRTs targeted in each procedure were susceptible to punishment.…”
mentioning
confidence: 99%